Pore Fluid Pressure Imaging of the Mt. Pollino Region (Southern Italy) From Earthquake Focal Mechanisms. Issue 22 (23rd November 2021) - De Matteis, R.; Convertito, V.; Napolitano, F.; Amoroso, O.; Terakawa, T.; Capuano, P.
Abstract: Focal mechanisms of selected earthquakes, recorded in the Mount Pollino region (southern Italy) from 2010 through 2014, are used to infer the pore fluid pressure at hypocenter depths. The 3‐D excess pore pressure field provides evidence that the sequence occurs in a fluid‐filled volume with values reaching 35 MPa. The mechanisms underlying this swarm‐like sequence and the triggering of earthquakes are investigated by computing the cumulative static Coulomb stress change at hypocenter depths and analyzing the pore‐pressure diffusion mechanism. The results indicate that static Coulomb stress change was lower than 0.01 MPa, which is the value generally assumed as threshold for the triggering, and seismicity distribution was actually driven by pore‐pressure diffusion with relatively low diffusivity value. This latter mechanism could also explain the delayed triggering of the two larger events M L 4.3 and M L 5.0, respectively, that occurred about 150 days apart. Plain Language Summary: Between 2010 and 2014, a seismic sequence of about 10, 000 small‐to‐moderate earthquakes was recorded in the Mount Pollino region, one of the most seismic hazardous areas of Italy. The physical mechanism underlying the swarm‐like sequence is not yet adequately understood, and in this study, the role of fluids is investigated. The 3D distribution of the pore fluid pressure, obtained from focal mechanisms, evidences that the sequence occurred in a fluid‐filled volume at pressure higher than hydrostatic value, and explains the triggering of events also on faults non‐optimally oriented with respect to the regional stress pattern. Furthermore, the timing of the sequence evolution is studied by exploiting the contribution of Coulomb static stress change and the role of pore‐pressure diffusion mechanism. Key Points: Pore pressure imaging of Mt. Pollino evidences that seismic sequence occurred in a fluid‐filled volume at pressure higher than hydrostatic Pore pressure diffusion analysis suggests that seismicity distribution was driven by relatively low diffusivity value